Structural and Thermal Properties of Li2O-Na2O-P2O5 Glasses Doped with La2O3 - Chen, Peipei; Wu, Haitao; Qu, Ya; Yue, Yunlong (Asian Journal of Chemistry, 2015)
Glasses of general formula (1-x)(0.5P2O5-0.25Na2O-0.25Li2O)-xLa2O3 with x = 0, 0.5, 1.0, 1.5 and 2.0 mol % were prepared by the traditional melting-quenching method. Fourier transform infrared spectrum and differential thermal analysis have been investigated, meanwhile density and molar volume (Vm) have been analyzed. The FTIR spectra show that the structure of glass has little changes after doping with lanthanum ions for all glass samples. The results of density show minimum and the values of Vm observe maximum when doping 1 mol % La2O3. The glass transition, Tg and Tc-Tg indicate that the glass doping 1 mol % La2O3 had better glass-forming ability than other samples.